Respon Desa Adat Terhadap Perkembangan Pariwisata di Desa Adat Manuaba, Desa Kenderan, Kabupaten Gianyar - Ratni, Ni Wayan; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2021)
Various tourist destinations based culture can be found in Bali. One of them is Manuaba villages in Tegalalang Gianyar Regenc. Manuaba is one of the villages which have already started to be influenced by tourism. The majority of the livelihoods of Indigenous Village Manuaba was agriculture. Along with the influx of tourism there is a change in the way the community point of view, investors are starting to get in and the farmers start to sell their land to the investors. Most of the investors build an acomodation on the agricultural land.This research used qualitative methods with of observation techniques, interview techniques and the study of documents. Sample techniques used purposive sampling for determinate informants. Based of the research results that the public began to feel the impact of the changes of the land function. Communities creating a perarem to limit the new building in the agricultural land. There are some suggestions that are proposed to the Government the more sensitive areas to monitor the development of the tourism in Bali. Key Words : investors, the conversion of agricaltural land functions, tourism, perarem, society.